Freedom of Expression in Various Political Systems in today’s Digital Age: A Comparative Case Study : आज के डिजिटल युग में विभिन्न राजनीतिक प्रणालियों में अभिव्यक्ति की स्वतंत्रता: एक तुलनात्मक केस अध्ययन - Rathore, Shipra; Soni, Rupam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper is an attempt to conduct a comparative analysis of the status of freedom of expression in the current global scenario, focusing on the governance systems of India, the United States of America, Russia, and China. Freedom of expression is a fundamental pillar of democracy, empowering citizens to express their views freely and ensure governmental accountability. This study employs the theoretical frameworks of liberalism, authoritarianism, and deliberative democracy to understand how different political systems and cultural heritages influence this right. The comparative analysis method has been used for this case study. The conclusion of the paper highlights that in the global era, freedom of expression has assumed a multidimensional character due to the broad role of the welfare state, the individual leadership capacities of political leaders, citizens' awareness, divisive sentiments on sensitive issues, and the impact of commercial and economic policies on the media. Abstract in Hindi Language: आज के वैश्विक परिदृश्य में अभिव्यक्ति की स्वतंत्रता की स्थिति का तुलनात्मक विश्लेषण करने के उद्देश्य से यह शोधपत्र एक प्रयास है, जिसमें भारत, संयुक्त राज्य अमेरिका, रूस और चीन की शासन व्यवस्था का शोधार्थी द्वारा अध्ययन किया गया। अभिव्यक्ति की स्वतंत्रता लोकतंत्र का आधारभूत तत्व है, जो नागरिकों को स्वतंत्र रूप से विचार व्यक्त करने और सरकार की जवाबदेही सुनिश्चित करने में सशक्त बनाती है। यह अध्ययन उदारवाद, सत्तावाद और विचार-विमर्शात्मक लोकतंत्र के सैद्धांतिक ढांचे का उपयोग करता है, ताकि यह समझा जा सके कि विभिन्न राजनीतिक व्यवस्थाएं और सांस्कृतिक धरोहर इस अधिकार को कैसे प्रभावित करते हैं। इस शोधपत्र के लिए तुलनात्मक विश्लेषण पद्धति का उपयोग किया गया है। शोधपत्र का निष्कर्ष यह दर्शाता है कि वैश्विक युग में लोककल्याणकारी राज्य की व्यापक भूमिका, नेताओं की व्यक्तिगत नेतृत्व क्षमता, नागरिकों की जागरूकता, संवेदनशील मुद्दों पर विभाजनकारी भावनाऍ, साथ ही वाणिज्यिक व आर्थिक नीतियों का मिडिया पर प्रभाव –इन सभी के कारण अभिव्यक्ति की स्वतंत्रता एक बहु आयामी रूप ले चुकी है । Keywords: अभिव्यक्ति की स्वतंत्रता, लोकतंत्र, सत्तावाद, उदारवाद, मौलिक अधिकार